Microbiological Quality and Adulteration of Pasteurized and Raw Milk Marketed in Dharan, Nepal - Limbu, Dhiren Subba; Bantawa, Kamana; Limbu, Dil Kumar; Devkota, Mandira; Ghimire, Monika (Himalayan Journal of Science and Technology, 2020)
This study was aimed to evaluate the quality of raw and pasteurized milk marketed in Dharan. Milk may be contaminated with pathogenic microorganisms and a mixture of several adulterants and such milk pose a risk to consumers. The study was carried out from September 2019 to January 2020. Collected samples were tested for adulterants (starch, formalin, neutralizer and table sugar) as well as microbial quality (Total Coliform count, Total Viable Count, Thermoduric Count, Escherichia. coli and Staphylococcus aureus) as per standard guideline. The adulterants starch, formalin and neutralizer were not detected in both raw and pasteurized milk. However, table sugar was present in 45% (9 out of 20) raw milk and 90% (18 out of 20) pasteurized milk. The average Total Viable Count, Total Coliform Count and Thermoduric Count of raw milk were, 59×105 CFU/ml, 14×104 CFU/ml and 5×103 CFU/ml respectively. Similarly, the average Total Viable Count, Total Coliform Count and Thermoduric Count of pasteurized milk were found to be 15×104 CFU/ml, 14×103CFU/ml and 4×103 CFU/ml respectively. E. coli was detected in 30% pasteurized milk whereas S. aureus was isolated from only 20%. Likewise, E.coli and S. aureus were found in 55% and 45% of raw milk respectively. The results of the study indicated that routine monitoring of dairy industries and raw milk vendors, awareness campaign and good hygienic practice should be promoted to upgrade the quality of raw and pasteurized milk.